Dynamic matching in campus placements: The benefits and affordability of the dream option. Issue 3 (September 2022) - Ranjan, Ashutosh; Gujar, Sujit; Ramani, Vinay
Abstract: We propose a new approach to improving student outcomes - the provision of the dream option that allows a student with a job offer to participate in the placement process again. Comparing three different student preference structures, we show that the dream option improves stability; however, it does not always improve student happiness and rank efficiency. Nevertheless, imposing a particular structure on student preferences, namely the sequential preference condition, improves both student happiness and rank efficiency. We recommend when to use the dream option and when not to use it.